Heparin-conjugated alginate multilayered microspheres for controlled release of bFGF. (4th June 2015) - Zuo, Qinhua; Guo, Rui; Liu, Quan; Hong, An; Shi, Yunfeng; Kong, Qian; Huang, Yuexin; He, Liumin; Xue, Wei
Abstract: In order to effectively immobilize and control release of basic fibroblast growth factor (bFGF) from alginate microspheres, heparin-conjugated alginate (H-Alg) was first synthesized by covalent binding. Then multilayered H-Alg microspheres (multilayered microspheres) were fabricated via an electrostatic droplet generation technique followed by a layer-by-layer (LbL) self-assembly technique. Several techniques such as Fourier transform infrared spectroscopy (FTIR), 1 H-NMR, zeta potential analysis and scanning electron microscopy (SEM) were used to characterize the properties of H-Alg (FTIR and 1 H-NMR) and multilayered microspheres (FTIR, zeta potential analysis and SEM). bFGF binding efficiency, release profiles of bFGF from multilayered microspheres and the biological activity of released bFGF were well investigated. It was found that the bFGF binding efficiency of H-Alg microspheres was increased up to five times higher than that of the alginate microspheres. Additionally, the release profiles of bFGF from multilayered microspheres were sustained for two weeks with relieved initial burst release, and the release rate to bFGF could be regulated by controlling the number of deposited layers. Importantly, the released bFGF still retained its biological activity as assessed by the in vitro proliferation of NIH-3T3 mouse fibroblasts. In conclusion, this study presented an easy yet effective method for the controlled, sustained release of heparin-binding growth factors, using polyelectrolyte multilayer-coated heparin-conjugated alginate microspheres.